Hubungan Penerapan SOP Perawatan Luka dengan Tingkat Kepuasan Pasien Ulkus Diabetukum - Suwanto, Suwanto; Wulandari, Rizki Yeni (Utan Kayu Publishing, 2021)
With the increasing public demand for the quality of health services, the service function needs to be improved for providing patient satisfaction. Based on the results of 2015 data from health services focused on wound nursing services in Bogor Indonesia there are 148 patients there are 148 diabetic ulcer patients. At Takhir Clinic in 2020, 227 patients were injured with a diagnosis of Diabetic Ulcer. The quality of service consisting of many people can be mutually uniformed and improved by applying Standard Operational Procedures (SOP) that are prepared with applicable provisions. This study aims to find out the relationship of the application of wound care SOP with the level of patient satisfaction of Diabetukum. This research is a type of quantitative research, using a cross sectional study design with a sample number of 64 respondents determined by accidental sampling techniques by conducting interviews using questionnaires. This research was conducted. The results showed that there is a meaningful relationship between compliance with the application of wound care SOPs with the satisfaction of Diabetukum Ulcer patients with p-Value less than 0.001. Finally, it is expected that Takhir Lampung Timur Clinic can continue to maintain and improve the quality of services through the identification of factors that affect compliance in the application of wound care SOPs.